2022
DOI: 10.7759/cureus.23191
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of High-Intensity Preoperative Physiotherapy Training on Postoperative Outcomes in Greek Patients Undergoing Total Knee Arthroplasty: A Quasi-Experimental Study

Abstract: Purpose: Several studies have shown that patients with severe osteoarthritis (OA) of the knee can reduce their knee pain, improve their quadriceps strength, and improve their functional ability through regular exercise training. The purpose of this study was to investigate the efficacy of a six-week supervised highintensity preoperative training program on muscle strength, functional performance, and patient-reported outcomes in patients undergoing total knee arthroplasty (TKA).Methods: Ninety-eight patients s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Prior investigation showed that pre-operative exercises could enhance self-reported knee function, positive outcomes in RTS, and prevent PTOA 93) . Furthermore, pre-operative exercises could minimize lower limb neuromuscular function degradation after surgery 94) . There are two phases of pre-operative treatment of ACLR 95) .…”
Section: Preventive Strategies Of Poor Knee Functions and Osteoarthri...mentioning
confidence: 99%
“…Prior investigation showed that pre-operative exercises could enhance self-reported knee function, positive outcomes in RTS, and prevent PTOA 93) . Furthermore, pre-operative exercises could minimize lower limb neuromuscular function degradation after surgery 94) . There are two phases of pre-operative treatment of ACLR 95) .…”
Section: Preventive Strategies Of Poor Knee Functions and Osteoarthri...mentioning
confidence: 99%
“…Usually, increased physiotheist contact is thought to enhance the rehabilitation of OA patients after knee arthroplasty, especially prolonging postoperative inpatient rehabilitation. For instance, a quasi-experimental study form Dimitrios et al (Vasileiadis et al, 2022) demonstrated that a 6-week physical therapy program supervised by a physiotherapist before surgery is efficacious for decreasing pain, improving knee function, and enhancing living activities. However, recent studies suggested that inpatient or clinic-based rehabilitation offers no clinically important advantages when compared with homebased rehabilitation (Buhagiar et al, 2019).…”
Section: Clinical Studiesmentioning
confidence: 99%